HIGH JOB STRAIN AND RELATED FACTORS AMONG NURSES AT MEDICAL CENTERS IN HO CHI MINH CITY, 2025 (Tạp chí Y học Cộng đồng, 2026)
A multicenter cross-sectional study was conducted at medical centers in Ho Chi Minh City from December 2024 to December 2025. The study included 768 nurses who were surveyed using a self-administered questionnaire on high job strain among nurses. The objective of the study was to determine the prevalence of high strain job and related factors among nurses working at medical centers in Ho Chi Minh City in 2025. The results showed that the prevalence of high job strain among nurses was 6.3%. Nurses with low job control and low job comfort accounted for high proportions, at 57.6% and 54.4%, respectively. Nurses experiencing high physical workload accounted for 31.6%, while those with high decision-making authority and high social support accounted for 85.4% and 81.0%, respectively. Regarding psychological stress status, nurses with active jobs accounted for 42.4%, and those perceiving high job strain accounted for 6.3%. Nurses with 3–6 years and 6–9 years of working experience in their departments had higher work pressure compared to those with less than 3 years of experience. Nurses working in administrative, support, and paraclinical departments experienced higher work pressure than those working in clinical departments. Nurses working 41–48 hours per week and more than 48 hours per week had higher work pressure than those working ≤40 hours per week. Nurses who concurrently performed additional duties experienced higher work pressure than those without additional responsibilities, with p < 0.0
Keywords: High job strain, nurses, related factors.